Estimation of critical metal stock and recycling potential in China’s automobile industry - Li, Yang; Liu, Yanhui; Huang, Shiyu; Sun, Liangfan; Ju, Yiyi (Frontiers in Environmental Science, 2022)
The rapid expansion of electric vehicles (EVs) will place huge pressure on the demand for critical metals, at the same time, provide a huge potential for recycling critical metals from them. Long-term predictions of stock and recycling potential can effectively reveal the supply risk of critical metals. In this study, we identified the critical metals in the electrification transformation of the automobile industry and estimated the stock of critical metals from 2022 to 2050 under multiple scenarios in China. This study also estimated the economic value and discussed the maximum recycling potential of critical metals in EVs. The results show that China’s passenger vehicles will reach 547.5-623.8 million in 2050. According to China's current energy conservation and emission reduction policies, the fuel vehicle (FV) ownership will peak in 2042, at 488.2 million. If strict energy conservation and emission reduction policies are adopted, EV ownership will increase from 148.3 million to 293.9 million by 2050, leading to a rapid increase in the stock of critical metals. The total stock of key critical metals under the scenario with stringent policies will be 29.27 million tons in 2050, 10.55 million higher compared to the scenario with no ban on fuel vehicles. This study provides references for the sustainable supply of critical metals that are required for the electrification transformation and sustainable development in the automobile industry.